Development of Rural Economy Through Banking Reforms in India - Mohan, Mayank; Chaudhary, Shivani (Journal of Commerce and Trade, 2008)
Development of rural areas in India is slow because we have concentrated mainly on urban development in our country. Rural infrastructure is not only a key component of rural development but also an important ingredient in ensuring any sustainable poverty reduction programme. The development of infrastructure and newer agricultual techniques in rural areas will improve rural economy, employment and quality of life. i Rural industrialization is also another area which will prove helpful in providing employment, removing poverty and thus the development of rural areas. Further, our village cottage industries that have become outdated due to lack of modernization should be aided, so that our huge labour resource may be employed. Immigration of educated people to the cities makes the situation worst. Though there are handful of rural people who can afford to have education in the cities yet when they get the chance they prefer to settle down in cities only due to lack of employment opportunities and poor standard of living in rural areas. Our rural economy is underdeveloped due to the shortage of finance. The poor rural people are not in a position to start new businesses due to lack of initial and working capitals with them. Banks can help them to overcome this problem. The main objective of establishing the regional rural banks is to provide credit and other facilities, especially to the small and marginal farmers, agricultural labourers, artisans and small entrepreneurs in the rural areas, who are under the shortage of funds.